NATIONAL-CULTURAL FEATURES OF AGRICULTURAL TERMINOLOGY IN ENGLISH AND UZBEK (International Conference on Economics, Finance, Banking and Management, 2025)
This article presents a comparative analysis of the national and cultural features of agricultural terminology in the English and Uzbek languages. The study examines the sources of formation, historical layers, and linguocultural characteristics of both terminological systems. The agricultural lexicon of English is largely rooted in Anglo-Saxon origins and enriched with borrowings from Romance languages, while Uzbek predominantly contains native Turkic terms along with Arabic, Persian, Russian, and modern English borrowings. Through examples, the paper highlights semantic differences of certain concepts in both languages, translation challenges of cultural-specific words (realia), and the impact of socio-historical factors on the development of terminological systems.